Northern Sweden Diet Database (NSDD) - Johansson, Ingegerd; Winkvist, Anna (Umeå University, 2016)
NSDD is a database with harmonised data from two population based projects ”Västerbotten Intervention Project” och ”MONICA in northern Sweden”. Information is collected by a validated, semi-quantitative, food frequency questionnaire (FFQ). Data collection is done by identical instrument and in the same manner in the two projects. The FFQ has three main sections: portion size indication for staple foods, intake frequencies, and dietary supplements. Some information on dietary and meal regimens is available. In addition to information on intake frequencies of single food items or food groups, estimated energy and nutrient intake and a selection of dietary indexes are available.

Enheten för biobanksforskning (EBF) handhar databasen, medan Västerbottens läns landsting ansvarar för insamling och förvaring av biobanksmaterial.

The Västerbotten Intervention Project (VIP) och MONICA are population based projects studying life habits in the population and to reduce the incidence of cardio metabolic diseases. Detailed information on the two projects can be found at their respective website. These are reached via http://www.biobank.umu.se/

The dataset includes data regarding intakes of food items, nutrients, calculated diet indexes and intake of food supplements. Data are collected through self-reported questionnaire. The dataset growths by approximately 5000 observations per year and the proportion with repeated observations increases.

Clinical samples (plasma, serum and DNA) are not included in NSDD but handled separately, in a biobank (see http://www.biobank.umu.se/).



By January 2016, the combined VIP-MONICA diet dataset includes 121,996 unique subjects (equal proportion men and women) with at least one visit and a diet recording. Of these 8.2% are excluded because of incomplete food intake data, extreme (highest and lowest 1%) food Intake levels (FIL), extreme energy intakes (lowest 1% and >5,000 kcal). Nearly 40% have a second 10-year follow up and 7% a third 10-year follow-up.

Intakes are reported on a fixed 9-level scale: never, a few times/year, 1-3 times/month, 1 time/week, 2-3 times/week, 4-6 times/week, 1 time/day, 2-3 times/day, ≥4 times/day.

Variables in the dataset: 64-84 food items, 65 nutrients including alcohol, 12 on supplements, 3 diet indexes, In addition, some hundred variables on medical status, socio-economy, tobacco use, physical activity, etc. can be linked from VIP and MONICA.

NSDD är en databas som inkluderar harmoniserade data från de två befolkningsbaserade projekten ”Västerbotten hälsoundersökningar” och ”MONICA i norra Sverige”. Informationen samlas in med hjälp av en validerad, semi-kvantitativ, livsmedelsfrekvensenkät (FFQ). Insamlingen sker med identiskt instrument och på lika sätt i de två projekten. Kostenkäten består av tre huvudsektioner: portionsstorleksangivelse för baslivsmedel, intagsfrekvenser, och kosttillskott. Viss övergripande information inhämtas även kring speciella kost- samt måltidsvanor. Förutom information om intagsfrekvenser av enstaka livsmedel och livsmedelsgrupper, finns även skattade energi- och näringsintag och ett antal kostindex.

Enheten för biobanksforskning (EBF) handhar databasen, medan Västerbottens läns landsting ansvarar för insamling och förvaring av biobanksmaterial.

Västerbotten Intervention Project (VIP) och MONICA är befolkningsbaserade projekt med syfte att studera levnadsvanorna bland befolkningen och att med olika interventioner minska insjuknandet i hjärt- och kärlsjukdomar. Detaljerad information om de två projekten finns på respektive hemsida som nås via http://www.biobank.umu.se/

Datasetet innefattar uppgifter om intag av livsmedel, näringsämnen, beräknade kostindex och intag av kostsupplement. Data är insamlade via självrapporterade enkäter. Datasetet växer med ca 5000 observationer per år och en kontinuerligt ökande andel med upprepade besök.


Per januari 2016 finns 121,996 unika individer (lika andelar män och kvinnor) med åtminstone ett besök och en kostregistrering. Av dessa exkluderas 8.2% av kvalitetsskäl (inkomplett FFQ, extrema (högsta och lägsta 1%) av “food Intake levels” (FIL), extrema energiintag (lägsta 1% och >5,000 kcal). CA 40% har en 10-års uppföljning och 7% ytterligare en tredje 10-år uppföljning.

Intag rapporteras på en fast 9-gradig skala: aldrig, några ggr/år, 1-3 ggr/månad, 1 ggr/vecka, 2-3 ggr/vecka, 4-6 ggr/vecka, 1 ggr/dag, 2-3 ggr/dag, ≥4 ggr/dag.

Variabler i datasetet: 64-84 om livsmedel, 65 om näringsämnen inkluderande alkohol, 12 om supplement, 3 kostindex. Vidare finns några hundra variabler med medicinska mått, socio-ekonomi, tobaksbruk, fysisk aktivitet mm att tillgå via länkning till VIP och MONICA.

Kliniska prover (såsom plasma, serum och DNA) ingår inte i NSDD utan hanteras separat, i en biobank (se http://www.biobank.umu.se/ ).
Northern Sweden Diet Database (NSDD)
Keywords: Data Collection; Datainsamling; Diet Surveys; Kostundersökningar; Life Style; Livsstil; Longitudinal Studies; Longitudinella studier; Socioeconomic Factors; Socioekonomiska faktorer; Risk Factors; Riskfaktorer; Diet; Kost; Diabetes Mellitus; Diabetes; Physical Fitness; Fysisk kondition; Cardiovascular Diseases; Kardiovaskulära sjukdomar; Dietary Supplements; Kosttillskott; Energy Intake; Energiintag; Food; Livsmedel; Glycemic Index; Glykemiskt index; diet and exercise; motion och matvanor; food consumption; livsmedelskonsumtion; nutrient intake; näringsintag; food groups; livsmedelsgrupper; alcohol; alkohol; Food frequency questionnaire; livsmedelsfrekvensenkät; FFQ; FFQ; Swedish Diet Cohort Consortium (SDCC); Swedish Diet Cohort Consortium (SDCC); validated FFQ; validerad FFQ; HEALTH; HÄLSA; Health Sciences; Hälsovetenskap; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin